Resorbable osteosynthesis in mandibular fractures : an exploratory systematic review = Osteosíntesis reabsorbible en fracturas mandibulares : una revisión sistemática exploratoria - Sanino Zavala, Ignacio
Mandibular fractures have a high prevalence in the maxillofacial region, often requiring surgical intervention. The gold standard for treatment involves open reduction with osteosynthesis using titanium plates. New biocompatible materials have been applied to address the complications and disadvantages of titanium plates, leading to the emergence of absorbable osteosynthesis plates. Understanding the effectiveness of titanium plates and absorbable osteosynthesis plates in the treatment of mandibular fractures helps determine the need to invest in new techniques with predictable outcomes. To describe the effectiveness of using titanium plates and absorbable osteosynthesis plates in the treatment of mandibular fractures. In August 2023, an exploratory systematic review of the available literature since 2018 on the use of absorbable osteosynthesis plates in mandibular fractures was conducted. PubMed, Scopus, and WOS were searched, including studies in English or Spanish. A total of 227 articles were obtained. After reviewing titles and abstracts, 29 articles were included for full-text reading. Nine duplicates were discarded, and 10 were excluded based on predefined criteria, resulting in a total of 10 articles for this study. Authors report that titanium plates exhibit less displacement of the contact surface in fractured segments due to a larger surface area, rigidity, and load-bearing capacity. Absorbable osteosynthesis plates are more flexible but are susceptible to greater deformation under significant masticatory forces, potentially leading to fracture opening and displacement of bone segments. Postoperative complications were analyzed, and no statistically significant differences were found. Titanium and absorbable devices did not differ in terms of biomechanical behavior and postoperative complications in the treatment of mandibular fractures. Further studies comparing both types of plates in mandibular fractures are needed.